P495 Does drug level monitoring help us to understand the mechanism behind the superiority of combo therapy in inflammatory bowel diseases?. (16th January 2018) - Fábián, A; Szántó, K; Szíjártó, A L; Bor, R; Bálint, A; Farkas, K; Milassin, Á; Rutka, M; Szepes, Z; Földesi, I; Kata, D; Mezei, Z A; et al.
Abstract: Background: Clinical data suggest a synergistic effect between thiopurine and anti-tumour necrosis factor (anti-TNF) therapy both in ulcerative colitis (UC) and Crohn's disease (CD). In previous studies, azathioprine (AZA) metabolites and biological drug trough levels have not been investigated simultaneously to verify the mechanism behind the favourable outcomes. Methods: This prospective, cross-sectional study aimed to evaluate potential correlation between AZA metabolite (6-thioguanine nucleotide; 6-TGN) levels and anti-TNF drug (infliximab [IFX] and adalimumab [ADA]) serum trough levels. Consecutive IBD patients on maintenance AZA, IFX or ADA monotherapies, and on IFX/AZA or ADA/AZA combinations were prospectively enrolled. 6-TGN level was measured with high-performance liquid chromatography, and IFX and ADA levels were assessed by ELISA method. Anti-TNF drug (IFX or ADA) trough levels were compared in patients on IFX or ADA monotherapy with those on combined IFX/AZA or ADA/AZA therapy using one-way analysis of variance. Significance of correlation between 6-TGN level in patients on AZA monotherapy and those on combination therapy (IFX/AZA or ADA/AZA) was also assessed. Results: A total of 41 consecutive IBD (30 CD, 11 UC) patients were involved. Male/female ratio was 19 of 22, mean patient age was 36 years, and average disease duration was 10.3 years. Average CDAI score for CD patients was 99, and average partial Mayo score for UC patients was 1. Eleven patients were on maintenance AZA, 9 on IFX, and 6 on ADA monotherapies, 9 received IFX/AZA, and 6 ADA/AZA combination. No significant difference was found between IFX trough levels in those on combined IFX/AZA therapy compared with those on IFX monotherapy (5.34 ± 2.95 μg/ml vs. 7.32 ± 9.68 μg/ml, p = 0.526). Similar results were found in case of ADA trough levels (6.71 ± 2.98 µg/ml for ADA monotherapy vs. 5.87 ± 5.40 µg/ml for combined ADA/AZA therapy, p = 0.798). 6-TGN levels were lower in patients on combined IFX/AZA and ADA/AZA therapy (316 ± 33 pmol/8 × 10 8 RBC and 326 ± 9.9 pmol/8 × 10 8 RBC, respectively) compared with those on AZA monotherapy (428 ± 49.5 pmol/8 × 10 8 RBC). A slight negative correlation could be observed between 6-TGN levels and both IFX and ADA levels in patients on combination therapy (correlation coefficient −0.227 and −0.425 for IFX and ADA, respectively), but none proved to be significant ( p = 0.557 for IFX, and p = 0.401 for ADA). Conclusions: Preliminary results of our study suggest that favourable outcomes of thiopurine and anti-TNF combination therapy may not be related to a synergistic effect between AZA metabolites and IFX or ADA trough levels.